Improving returns to public investments in China’s agricultural sector - CGIAR Research Program on Policies, Institutions, and Markets (2018)
Recommendations to improve the effectiveness of China’s public expenditures in the agricultural sector were prepared by IFPRI’s China Strategy Support Program team using the Statistics on Public Expenditures for Economic Development database, and shared with the Government of China and the Asian Development Bank. In line with these recommendations, changes have taken place in the country’s public expenditure policies, some of which are reflected in China’s new Rural Revitalization Strategy.